The role of advanced practice nurses in improving healthcare outcomes for patients with chronic kidney disease: A scoping review protocol. - Hanako Nozu; Haruka Tamura; Takemi Kudo; Tomoko Araki; Hidetaka Sato; Takao Watanabe; Isoji Sasagawa (PLoS ONE)
Introduction The number of patients with chronic kidney disease is increasing worldwide; previous studies have suggested that advanced practice nurses, including nurse practitioners and clinical nurse specialists, with expert practice skills can provide high-quality care and solve complex healthcare problems. In general, nurse practitioners are generalist nurses who work as autonomous clinicians with whole personal care. Clinical nurse specialists, in contrast, are nurses with advanced nursing knowledge and skills for individuals or specific populations. Their roles are independent and different; however, similarities exist in their role in potentially improving healthcare outcomes. Although two previous studies described the role of nephrology nurse practitioners, they were systematic reviews, and their outcomes were limited. To clarify the overall aspect of advanced practice nurses' role, it is necessary to extract the studies illustrating advanced practice nurses' practices for patients with chronic kidney disease. Objective This study aims to map the literature describing the role of advanced practice nurses in improving healthcare outcomes for patients with chronic kidney disease. Materials and methods This scoping review will be conducted using the Joanna Briggs Institute methodology for scoping review. Online databases will be searched across MEDLINE (PubMed), CINAHL (EBSCOhost), Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, and Web of Science. Only studies published in English will be included, and no date limit will be set. Chronic kidney disease, renal replacement therapy, and advanced practice nurses as keywords and related search terms will be used. Two independent reviewers will screen the title and abstract/full-text; in case of discrepancy, a third reviewer will make the final decision. The results will be extracted and presented following the review question concerning the study characteristics, patients' characteristics, condition of chronic kidney disease, and role of advanced practice nurses.